The genes and enzymes of phosphonate metabolism by bacteria, and their distribution in the marine environment - Villarreal-Chiu, Juan F.; Quinn, John P.; McGrath, John W. (Frontiers in Microbiology, 2012)
Abstract Phosphonates are compounds that contain the chemically-stable carbon-phosphorus (C-P) bond. They are widely distributed amongst more primitive life forms including many marine invertebrates and constitute a significant component of the Dissolved Organic Phosphorus reservoir in the oceans. Virtually all biogenic C-P compounds are synthesized by a pathway in which the key step is the intramolecular rearrangement of phosphoenolpyruvate to phosphonopyruvate. However C-P bond cleavage by degradative microorganisms is catalysed by a number of enzymes – C-P lyases, C-P hydrolases and others of as-yet-uncharacterized mechanism. Expression of some of the pathways of phosphonate catabolism is controlled by ambient levels of inorganic P (Pi) but for others it is Pi-independent. Interrogation of currently-available whole-genome bacterial sequences indicates that some 10 % contain genes encoding putative pathways of phosphonate biosynthesis while approximately 40% encode one or more pathways of phosphonate catabolism. Analysis of metagenomic data from the Global Ocean Survey suggests that some 10% and 30%, respectively, of bacterial genomes across the sites sampled encode these pathways. Catabolic routes involving phosphonoacetate hydrolase, C-P lyase(s) and an uncharacterized 2-aminoethylphosphonate degradative sequence were predominant. These data indicate the likely importance of phosphonate-P in global biogeochemical P cycling, and by extension its role in marine productivity and in carbon and nitrogen dynamics in the oceans.